Advances in aptamer-based biosensors for monitoring foodborne pathogens - Tracy Ann Bruce-Tagoe
Biosensors are analytical devices for detecting a wide range of targets, including cells, proteins, DNA, enzymes, and chemical and biological compounds. They mostly rely on using bioprobes with a high binding affinity to the target for specific detection. However, low specificity and effectiveness of the conventional biosensors has led to the search for novel materials, that can specifically detect biomolecules. Aptamers are a group of single-stranded DNA or RNA oligonucleotides, that can bind to their targets with high specificity and serve as effective bioprobes for developing aptamer-based biosensors. Aptamers have a shorter production time, high stability, compared to traditional bioprobes, and possess ability to develop them for specific target molecules for tailored applications. Thus, various aptasensing approaches, including electrochemical, optical, surface plasmon resonance and chip-dependent approaches, have been investigated in recent times for various biological targets, including foodborne pathogens. Hence, this article is an overview of various conventional foodborne pathogen detection methods, their limitations and the ability of aptamer-based biosensors to overcome those limitations and replace them. In addition, the current status and advances in aptamer-based biosensors for the detection of foodborne pathogens to ensure food safety were also discussed.